Effects of herbal supplements on milk production quality and specific blood parameters in heat-stressed early lactating cows - Saleh, Ahmed Ali; Soliman, Mahmoud Mohamed; Yousef, Mohammed Farid; Eweedah, Nabil Mohammed; El-Sawy, Hanan Basiouni; Shukry, Mustafa; Wadaan, Mohammad A. M.; Kim, In Ho; Cho, Sungbo; Eltahan, Hossam M. (Frontiers in Veterinary Science, 2023)
The present study explored the influence of supplemental herbal mixtures on cow milk production, quality, and blood parameters in dairy cows under high ambient temperatures. Thirty Holstein cows were randomly assigned into three experimental groups of 10 each. The first control group was supplied with the commercial basal diet, whereas two treatment groups were provided with the commercial basal diet supplemented with 50 and 100 g/head/day of the herbal mixture, respectively. The results showed that the mixture of herbal supplementation did not influence weekly milk production. Milk total fat, triglyceride, and total protein values were not affected (p < 0.05) in cows fed on basal diets supplemented with herbal mixture; however, milk cholesterol was decreased significantly by 100 mg/head/day of the herbal mixture. On the other hand, lactose has increased significantly by adding 100 mg/head/day of herbal mixture. Furthermore, the total cholesterol level in serum was decreased by adding 100 mg/head/day of the herbal mixture, while plasma prolactin, cortisol, GOT, and GPT were unaffected. Regarding fatty acids (C18, C18:1 (c9), 18:1 (c11), 18:2 (c9, c12), 18:2 (t9, t12), and CLA (c9, t11)), there was no significant variation between the groups. Meanwhile, both C19:00 and 18:3 (c6, c9, and c12) were noticeably higher (p < 0.05) in the group that received 100gm, followed by 50 mg, compared to the control. In conclusion, the supplement with a herbal mixture positively affected milk quality by decreasing total cholesterol and increasing lactose, milk fatty acid profile by increasing unsaturated fatty acids content, and plasma cholesterol levels.